THE APPLICATION OF COMBINATION OF SOLID BOXES AND AIR BAGS TO SUPPORT THE UNSINKABLE SMALL PASSENGER BOAT - R Hetharia, Wolter; R de Fretes, Eliza; Gaspersz, Fella; Louhenapessy, Jandri (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2020)
Small fast passenger boats serve to carry passengers at certain routes particularly in short distance between the islands. The passengers preferred those transport modes due to its short travel time. In fact, there are many accidents occur during boat operation which end up with the loss of life and materials at sea. An intensive study was executed by the authors with the purpose to obtain an unsinkable boat. The boat data of existing boats were collected and be used for re-designing process. During the design process, some solid boxes, expanded bags were provided inside boat to reduce the incoming water. Meanwhile, the bags were fitted outside the boat (side floater) to provide additional buoyancy and righting moment for stability performance. A boat model was developed and tested to confirm the design results. In addition, a full-scale boat was developed and equipped with solid boxes, air bags and side floaters. The theoretical computation and extrapolated results from model proved that the required volume for inside solid boxes and air bags are 1.213 m3 and 0.511 m3 respectively. Meanwhile, the required volume of outside air bags is 0.357 m3. It was found that the total boat weight, passengers and incoming water of 4.259 tons are balanced by weight displacement of 5.025 tons. There was reserve buoyancy of 0.766 tons that supports the boat to be float and side floaters to prevent the boat from capsize. The result of sea trial showed that with all loading conditions the boat was still afloat (unsinkable).